Effective imaging examination evaluation method for surgical pathological complete responds of head and neck squamous cell carcinoma after neoadjuvant immunochemotherapy - Ning, Yudong; Song, Yixuan; He, Yuqin; Li, Han; Liu, Yang; Liu, Shaoyan (Frontiers in Oncology, 2025)
ObjectiveTo explore an effective method for imaging examinations to evaluate the surgical pathological complete response (PCR) in patients with head and neck squamous cell carcinoma (HNSCC) following neoadjuvant immunochemotherapy (NIC).MethodsHNSCC patients who underwent NIC and subsequent surgery from May 2021 to November 2024 were retrospectively analyzed. All patients underwent imaging examination evaluations, including enhanced computed tomography (CT) and enhanced magnetic resonance (MR) imaging both before and after NIC. The average value of the region of interest (ROI) was extracted from the imaging examinations. Clinical parameter-related data were collected. The paired chi-square test was performed to analyze the differences in complete response (CR) between imaging examinations and pathology according to the response evaluation criteria in solid Tumors version 1.1 (RECISTv1.1). The optimal cutoff values of the adaptive ROI average value were determined using receiver operating characteristic curves (ROC). Binary logistic regression was applied to analyze the relevant clinical factors of PCR.ResultsIn total, data from 81 patients with enhanced CT and enhanced MR were included in this study. Significant discrepancies in CR were observed between enhanced CT, MRI, and pathology (21.0% vs 42.0%, 8.6% vs 42.0%) (P < 0.05). The ROI average value ratio (before/after NIC) was associated with a better PCR. Specifically, ROI average value ratio ≥ 1.18 on enhanced CT (odds ratio [OR] 125.306,95% confidence interval [CI] 5.545-2831.633,P <0.001; PCR 80.6% vs 11.1%) or ROI value ratio ≥ 1.06 on T2-weighted image of enhanced MR (OR 144.822,95%CI 9.271-2262.326,P < 0.001; PCR 90.3% vs 12.0%) was noted.ConclusionBased on RECIST v 1.1, discrepancies in PCR were found between imaging examinations and surgical pathology of HNSCC after NIC. The ROI average value ratio (before/after NIC) was associated with a better PCR, with an enhanced CT ROI average value ratio ≥ 1.18 or the ROI average value ratio ≥ 1.06. Thus, RECIST v1.1 was demonstrated to be an inaccurate assessment method for PCR in HNSCC after NIC. The ROI average value ratio may have good diagnostic efficacy for PCR in HNSCC patients receiving NIC.